2017
DOI: 10.3892/or.2017.5379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of evodiamine and berberine on the interaction between DNMTs and target microRNAs during malignant transformation of the colon by TGF-β1

Abstract: The tissue microenvironment functions as a crucial player in carcinogenesis, and transforming growth factor-β1 (TGF-β1) within the microenvironment stimulates the formation of neoplasms. Using an in vitro model of malignancy induced by TGF-β1, we assessed the effect of evodiamine and berberine on the interaction between DNA methyltransferases (DNMTs) and target microRNAs (miRNAs) in the model. Colon tissues from neonatal rats 7 days of age were cultured and malignancy was induced by TGF-β1 in vitro for 48 h, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…In the present study, the effective anticancer activity of Evo, which may be mediated by BMP9 via the upregulation of HIF-1α to partly increase the activity of p53, was demonstrated in human colon cancer. It has been reported that Evo exhibits great anti-cancer activities in many types of cancer, such as tongue, breast, colon, prostate and lung cancer (9)(10)(11)(12)26,27). As far as colon cancer is concerned, the anticancer activity of Evo may be mediated by inactivating the NF-κB (9) or TGF-β1 (11), or activating the p53/p21/Rb pathway (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the effective anticancer activity of Evo, which may be mediated by BMP9 via the upregulation of HIF-1α to partly increase the activity of p53, was demonstrated in human colon cancer. It has been reported that Evo exhibits great anti-cancer activities in many types of cancer, such as tongue, breast, colon, prostate and lung cancer (9)(10)(11)(12)26,27). As far as colon cancer is concerned, the anticancer activity of Evo may be mediated by inactivating the NF-κB (9) or TGF-β1 (11), or activating the p53/p21/Rb pathway (12).…”
Section: Discussionmentioning
confidence: 99%
“…Evodiamine (Evo), a quinolone alkaloid extracted from traditional herbal medicine Evodia rutaecarpa (7), has multiple pharmacological actions and could be used for obesity, inflammation, infectious and cardiovascular diseases (8). A growing amount of evidence has indicated that Evo exhibits anticancer activity against various types of cancer, such as tongue, colon and breast cancer (9)(10)(11)(12). According to studies, this activity of Evo may be mediated by NF-κB (9), transforming growth factor β1 (TGF-β1) (11) and/or the p53/p21/Rb pathway (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β1 is a multifunctional cytokine that regulates cell growth, motility, differentiation, apoptosis and plays an important role in tumor cell proliferation, migration and invasion ( 23 25 ). TGF-β1 is frequently overexpressed in multiple malignancies, colorectal ( 26 ), pancreatic ( 27 ), liver ( 28 ) and ovarian cancer ( 29 31 ). Canonical TGF-β signaling pathways begin with activation of serine/threonine kinase receptors, followed by the phosphorylation of Smad2/3 and Smad4, which formed into a complex.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, both BBR and evodiamine increased the expression of DNMT1, DNMT3A, DNMT3B, and their target miRNAs. ese findings suggest that BBR and evodiamine suppress the onset and development of colon cancer by regulating the expression of DNMTs and miRNAs [50].…”
Section: Colorectal Cancermentioning
confidence: 88%